Quantum interference in interacting three-level Rydberg gases: coherent population trapping and electromagnetically induced transparency - Sevinçli, Sevilay; Ates, C.; Pohl, T.; Schempp, Hanna; Hofmann, Christoph S.; Günter, Georg; Amthor, Thomas; Weidemüller, Matthias; Pritchard, J. D.; Maxwell, D.; Gauguet, A.; Weatherill, K. J.; et al. (Journal of physics. B, Atomic, molecular and optical physics, 2011)
In this paper, we consider the effects of strong dipole-dipole interactions on three-level interference phenomena such as coherent population trapping and electromagnetically induced transparency. Experiments are performed on laser cooled rubidium atoms and the results compared to a many-body theory based on either a reduced many-body density matrix expansion or Monte Carlo simulations of many-body rate equations. We show that these approaches permit quantitative predictions of the experimentally observed excitation and transmission spectra. Based on the calculations, we moreover predict a universal scaling of the nonlinear response of cold Rydberg gases.